Penyuluhan Bahaya Seks Bebas dan Sexting pada Siswa di SMP Negeri 40 Bulukumba - Kasmiranti Kasmiranti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Adolescents are a vulnerable group to environmental influences and the development of digital technology, including exposure to promiscuous sexual behavior and sexting practices. Lack of knowledge regarding the health, psychological, social, and legal impacts of these behaviors can increase the risk of risky sexual behavior in adolescents. This community service activity aims to increase adolescent knowledge about the dangers of promiscuous sex and sexting through health education. The activity was carried out on Thursday, June 18, 2026, targeting 25 students in grade VIII C. The methods used included a pre-test, counseling using interactive lectures, discussions and questions and answers, and a post-test to evaluate the increase in participants' knowledge. The counseling material included the definition of promiscuous sex and sexting, the causal factors, the health, psychological, social, and legal impacts, and prevention efforts through healthy relationships and wise use of social media. The evaluation results showed an increase in participants' knowledge, where the good knowledge category increased from 20.0% at the pre-test to 84.0% at the post-test, while the poor knowledge category decreased from 44.0% to 0%. Furthermore, most participants were able to re-explain the meaning of casual sex and sexting, their impacts, and preventative measures. This activity demonstrated that health education is an effective method for increasing adolescents' knowledge about the dangers of casual sex and sexting, which is expected to foster healthier, more responsible, and wiser behaviors in digital media use.